ON THE RELATION BETWEEN LEGAL NORMS AND PRINCIPLES OF MERITOCRACY IN THE CIVIL SERVICE - Kusainova, Лаззат Абаевна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
Dynamic in contemporary society relationship requires systematic changes in the current legislation . This article discusses the practical application of labor law and legislation in the public service of the Republic of Kazakhstan . Labor legislation establishes mechanisms destination and movement of workers in the event of significant changes in working conditions. However, these mechanisms are not sufficiently implemented in legislation in the field of public service. In turn, this creates a conflict in the application of the law. The author has developed proposals for the consolidation of the legislation in the field of Public Service and Labour Code.